2015
DOI: 10.1016/j.ajpath.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Injury Molecule-1 Protects against Gα12 Activation and Tissue Damage in Renal Ischemia-Reperfusion Injury

Abstract: Ischemic acute kidney injury is a serious untreatable condition. Activation of the G protein α12 (Gα12) subunit by reactive oxygen species is a major cause of tissue damage during renal ischemia-reperfusion injury. Kidney injury molecule-1 (KIM-1) is a transmembrane glycoprotein that is highly up-regulated during acute kidney injury, but the physiologic significance of this up-regulation is unclear. Here, we report for the first time that Kim-1 inhibits Gα12 activation and protects mice against renal ischemia-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 29 publications
(46 reference statements)
9
52
0
1
Order By: Relevance
“…The results of our previous meta-analysis indicated that urinary KIM-1 was an efficient novel urinary biomarker for the diagnosis of AKI [8]. Ismail et al [27] reported that KIM-1 provided endogenous protection against renal ischaemia-reperfusion injury by inhibiting G proteinα12. However, these studies focused mainly on the expression and function of KIM-1 at certain disease stages.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our previous meta-analysis indicated that urinary KIM-1 was an efficient novel urinary biomarker for the diagnosis of AKI [8]. Ismail et al [27] reported that KIM-1 provided endogenous protection against renal ischaemia-reperfusion injury by inhibiting G proteinα12. However, these studies focused mainly on the expression and function of KIM-1 at certain disease stages.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Sox9 driven Cre-ER 2 model crossed with R26R-tdTomato, Kumar et al showed that PT cells that initiated de novo expression of Sox9 after injury, contributed the most to repair, further implicating dedifferentiation as the predominant mechanism of epithelial repair [7]. Additionally, both PT-specific deletion of Sox9 in repair, and global deletion of Kim-1 during injury, exacerbated injury and delayed repair [79]. …”
Section: Tubular Injury and Repairmentioning
confidence: 99%
“…[17][18][19] It is important to note that primary PTECs are entirely dependent on KIM-1 for efferocytosis. 20 Work by our group and that of Bonventre confirmed that, compared to wild-type mice, both KIM-1-deficient mice 20 and mice expressing a mucin domain deletion (mutant) 21 are more prone to ischemic acute kidney injury owing to 2 major mechanisms trig- 18 KIM-1 expression, or lack thereof, likely does not contribute to renal pathology in native conditions, as no differences in kidney function or pathology between wild-type and KIM-1-deficient mice were observed prior to IRI induction.…”
Section: Introductionmentioning
confidence: 99%